(untitled) (Atti del Sodalizio Glottologico Milanese, 2019)
Grassmann’s Law ‒ the phonetic change by virtue of which in an original diaspirate root a (regressive) dissimilation process takes place ‒ is generally regarded as working in reduplicated verbal forms, see e.g. τίθημι < */thitheːmi/, πέφευγα < */phepheuga/ and so on. In this paper, I would argue in favour of the morphological nature of the process that generates non aspirated segments in the reduplicant. Indeed, the reduplicant is typologically characterized by the presence of unmarked features: among these, the non-aspirated stops can be included, if compared with the respective aspirated ones. KEYWORDS: Dissimilation, Grassmann’s Law, phonetic laws, markedness, reduplication